2017
DOI: 10.1186/s12879-017-2456-z
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan catabolism and immune activation in primary and chronic HIV infection

Abstract: BackgroundKynurenine/Tryptophan ratio (KTR) is increased in HIV infection, and linked to immune activation. We hypothesized that early cART initiation results in lower KTR compared to late initiation. Furthermore, we hypothesized that KTR prior to cART is a predictor of the magnitude of subsequent reduction in immune activation.MethodsProspective study including 57 HIV-infected individuals (primary HIV infection (N = 14), early presenters (>350 CD4+ T cells/μL, N = 24), late presenters (<200 CD4+ T cells/μL, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“… 50 Kynurenine/tryptophan is a general measure of indole 2,3-dioxygenase (IDO) which has an immunoregulatory role and is induced by interferon-gamma in response to viral infection. 49 IDO is responsible for the conversion of tryptophan to kynurenine and is a negative regulator of inflammation and this plays a significant role in limiting lung inflammation, but this is clearly perturbed given the elevated levels of Glyc A.…”
Section: Resultsmentioning
confidence: 99%
“… 50 Kynurenine/tryptophan is a general measure of indole 2,3-dioxygenase (IDO) which has an immunoregulatory role and is induced by interferon-gamma in response to viral infection. 49 IDO is responsible for the conversion of tryptophan to kynurenine and is a negative regulator of inflammation and this plays a significant role in limiting lung inflammation, but this is clearly perturbed given the elevated levels of Glyc A.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic immune activation is a feature of chronic HIV infection and determines the rate of disease progression [17, 18, 40]. HIV-2 infection has been reported to be associated with slower disease progression as compared to HIV-1.However the data available with respect to immune activation associated with infection is limited, conflicting and has reported on either CD4 or CD8 compartment in isolation [41–44].…”
Section: Discussionmentioning
confidence: 99%
“…Specific mechanisms of immune impairment are beyond the scope of this review; however, it is noted that aspects of T cell exhaustion persist in the face of chronic immune activation (Brenchley et al, 2006; Doitsh et al, 2014; Doitsh and Greene, 2016; Sokoya et al, 2017). In the last three decades, a wealth of information has indicated that IDO activation and its associated metabolites play a role in human HIV infection and early progression to AIDS (Fuchs et al, 1990; Hunt et al, 2014; Jenabian et al, 2015; Mehraj and Routy, 2015; Gelpi et al, 2017). Tryptophan catabolism and its immune-regulatory effect are notable during HIV progression (Almeida et al, 2009; Mehraj and Routy, 2015; Gelpi et al, 2017; Gautam et al, 2018).…”
Section: Tryptophan Catabolism In Hiv Infectionmentioning
confidence: 99%
“…In the last three decades, a wealth of information has indicated that IDO activation and its associated metabolites play a role in human HIV infection and early progression to AIDS (Fuchs et al, 1990; Hunt et al, 2014; Jenabian et al, 2015; Mehraj and Routy, 2015; Gelpi et al, 2017). Tryptophan catabolism and its immune-regulatory effect are notable during HIV progression (Almeida et al, 2009; Mehraj and Routy, 2015; Gelpi et al, 2017; Gautam et al, 2018). There is a strong association of elevated IDO activity with AIDS-defining illnesses (Nagamatsu and Schust, 2010; Catalfamo et al, 2012; Martinez and Gordon, 2014; Sokoya et al, 2017).…”
Section: Tryptophan Catabolism In Hiv Infectionmentioning
confidence: 99%